Nebulized and intravenous enzyme replacement therapy in mice with mucopolysaccharidosis type II - Alex J. Shamoun; Gisienne Reis; Malaica Ashley; Anatalia Labilloy; Leonardo F. Ferreira (PLoS ONE, 2025)
Mucopolysaccharidosis Type II is a hereditary lysosomal storage disease characterized by deficiency in the enzyme iduronate 2-sulfatase (IDS). IDS is critical in the breakdown of sulfated glycosaminoglycans and its deficiency leads to an accumulation of these compounds across various tissue types resulting in multisystemic dysfunction. Intravenous administration of recombinant IDS (idursulfase) substantially improves patients’ quality and length of life. However, recombinant IDS delivered intravenously is sequestered in the liver and respiratory failure remains as the leading cause of death for patients independent of idursulfase treatment, which suggests insufficient delivery to the lungs. This study aimed to assess a novel method of idursulfase administration using a nebulizer in combination with intravenous treatment and determine if this combination may improve lung delivery of idursulfase and overall pathology. Whole body IDS knockout mice underwent twelve weeks of intravenous, combination treatment, or vehicle injection and we harvested liver and lungs seven days after the last treatment for assessment of IDS activity, histological markers, and global proteomics for comparison with wild-type mice. Combination treatment increased IDS enzyme activity in the liver but not lungs Proteomics data demonstrated attenuation of key features of the disease in liver (metabolic pathways) and lungs (glycosaminoglycan pathways) with both treatments. Overall, adding nebulized administration of IDS did not lead to sustained increase in enzyme activity in the lungs but caused persistent modifications in glycosaminoglycan degradation pathway suggesting additional benefits to intravenous administration alone.